Neurophysiological Changes After Paired Brain and Spinal Cord Stimulation Coupled With Locomotor Training in Human Spinal Cord Injury - Pulverenti, Timothy S.; Zaaya, Morad; Grabowski, Monika; Grabowski, Ewelina; Islam, Md. Anamul; Li, Jeffrey; Murray, Lynda M.; Knikou, Maria (Frontiers in Neurology, 2021)
Neurophysiological changes that involve activity-dependent neuroplasticity mechanisms via repeated stimulation and locomotor training are not commonly employed in research even though combination of interventions is a common clinical practice. In this randomized clinical trial, we established neurophysiological changes when transcranial magnetic stimulation (TMS) of the motor cortex was paired with transcutaneous thoracolumbar spinal (transspinal) stimulation in human spinal cord injury (SCI) delivered during locomotor training. We hypothesized that TMS delivered before transspinal (TMS-transspinal) stimulation promotes functional reorganization of spinal networks during stepping. In this protocol, TMS-induced corticospinal volleys arrive at the spinal cord at a sufficient time to interact with transspinal stimulation induced depolarization of alpha motoneurons over multiple spinal segments. We further hypothesized that TMS delivered after transspinal (transspinal-TMS) stimulation induces less pronounced effects. In this protocol, transspinal stimulation is delivered at time that allows transspinal stimulation induced action potentials to arrive at the motor cortex and affect descending motor volleys at the site of their origin. Fourteen individuals with motor incomplete and complete SCI participated in at least 25 sessions. Both stimulation protocols were delivered during the stance phase of the less impaired leg. Each training session consisted of 240 paired stimuli delivered over 10-min blocks. In transspinal-TMS, the left soleus H-reflex increased during the stance-phase and the right soleus H-reflex decreased at mid-swing. In TMS-transspinal no significant changes were found. When soleus H-reflexes were grouped based on the TMS-targeted limb, transspinal-TMS and locomotor training promoted H-reflex depression at swing phase, while TMS-transspinal and locomotor training resulted in facilitation of the soleus H-reflex at stance phase of the step cycle. Furthermore, both transspinal-TMS and TMS-transspinal PAS and locomotor training promoted a more physiological modulation of motor activity and thus depolarization of motoneurons during assisted stepping. Our findings support that targeted non-invasive stimulation of corticospinal and spinal neuronal pathways coupled with locomotor training produce neurophysiological changes beneficial to stepping in humans with varying sensorimotor function after SCI.